2020
DOI: 10.1097/cm9.0000000000000932
|View full text |Cite
|
Sign up to set email alerts
|

Potential contribution of the gut microbiota to hypoglycemia after gastric bypass surgery

Abstract: Obesity has become a global health problem. Lifestyle modification and medical treatment only appear to yield short-term weight loss. Roux-en-Y gastric bypass (RYGB) is the most popular bariatric procedure, and it sustains weight reduction and results in the remission of obesity-associated comorbidities for obese individuals. However, patients who undergo this surgery may develop hypoglycemia. To date, the diagnosis is challenging and the prevalence of post-RYGB hypoglycemia (PRH) is unclear. RYGB alters the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 103 publications
(125 reference statements)
0
5
0
Order By: Relevance
“…Intestinal flora are an important part of the intestinal mucosal barrier, and disturbance of the intestinal flora can increase the risk of perioperative complications (28,29). Gastrointestinal surgery will destroy the intestinal mucosal barrier and increase the risk of postoperative pulmonary infection, anastomotic leakage and other complications (30). Some research has also confirmed that the cell-mediated immune response was impaired, the numbers of CD4 + and CD4 + /CD8 + T cells decreased, and the intestinal barrier function was damaged in patients with EC after laparoscopic Ivor-Lewis surgery (31).…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal flora are an important part of the intestinal mucosal barrier, and disturbance of the intestinal flora can increase the risk of perioperative complications (28,29). Gastrointestinal surgery will destroy the intestinal mucosal barrier and increase the risk of postoperative pulmonary infection, anastomotic leakage and other complications (30). Some research has also confirmed that the cell-mediated immune response was impaired, the numbers of CD4 + and CD4 + /CD8 + T cells decreased, and the intestinal barrier function was damaged in patients with EC after laparoscopic Ivor-Lewis surgery (31).…”
Section: Discussionmentioning
confidence: 99%
“…These include changes in bile acid composition and metabolism, which can modulate both GLP-1 and FGF-19, 20 and microbiome diversity and composition. 21,22 Interestingly, a recent study reports that individuals post-bariatric surgery who have undergone cholecystectomy (vs those without cholecystectomy) have significantly increased risk for both PBH and dumping syndrome, further supporting the potential role of changes in the kinetics or composition of circulating or enteral bile acids in the pathogenesis of PBH. 21,23 Likewise, differences in the microbiome may contribute to interindividual differences in glycemic and hormonal response to meals.…”
Section: Etiologymentioning
confidence: 99%
“…21,22 Interestingly, a recent study reports that individuals post-bariatric surgery who have undergone cholecystectomy (vs those without cholecystectomy) have significantly increased risk for both PBH and dumping syndrome, further supporting the potential role of changes in the kinetics or composition of circulating or enteral bile acids in the pathogenesis of PBH. 21,23 Likewise, differences in the microbiome may contribute to interindividual differences in glycemic and hormonal response to meals. Fermentation products of the microbiome, such as short chain fatty acids (SCFA), which are increased after RYGB, 24 can stimulate GLP1 release, 25 and may modulate insulin secretion, 6,27 potentially contributing to altered glucose metabolism.…”
Section: Etiologymentioning
confidence: 99%
“…17,18 Postprandial rises in glucose and exaggerated secretion of the incretin hormone glucagon-like peptide-1 (GLP-1) together trigger excessive secretion of insulin and subsequent rapid drops in glucose levels. 19,20 Additional contributors to PBH may include reduction in counterregulatory hormone response, 21,22 including blunting of hepatic glucose production during hypoglycaemia, 23 shifts in the gut microbiome 24 and alterations in the bile acid-FXR-FGF19 axis. [25][26][27] Unfortunately, PBH is a chronic condition and long-term treatment options are often incompletely effective but include dietary modification to reduce high-glycaemic-index carbohydrate intake and to ensure adequate protein and micronutrient intake, 28 acarbose or miglitol to slow carbohydrate absorption, 29 and somatostatin analogues (eg, octreotide or pasireotide) 30 and diazoxide 31,32 to reduce insulin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Postprandial rises in glucose and exaggerated secretion of the incretin hormone glucagon‐like peptide‐1 (GLP‐1) together trigger excessive secretion of insulin and subsequent rapid drops in glucose levels 19,20 . Additional contributors to PBH may include reduction in counterregulatory hormone response, 21,22 including blunting of hepatic glucose production during hypoglycaemia, 23 shifts in the gut microbiome 24 and alterations in the bile acid‐FXR‐FGF19 axis 25‐27 …”
Section: Introductionmentioning
confidence: 99%